Acute appendicitis and acute mesenteric adenitis in children: Are they clinically distinguishable? - Pokhrel, Manish (Journal of Kathmandu Medical College, 2020)
Background: Acute appendicitis and acute mesenteric adenitis have very similar clinical presentations but radically different treatment approaches in children. Objectives: This study aims to test the possibility of clinically distinguishing between acute appendicitis and acute mesenteric adenitis. Methodology: A cross-sectional study was designed to recruit all children (<16 years) presenting to Kathmandu Medical College Teaching Hospital with acute abdominal pain between July 2019 and November 2019. An initial diagnosis was made using clinical and laboratory data. Then all patients were subjected to ultrasound evaluation. The final diagnosis was based on the radiological or histopathological examination. The Paediatric Appendicitis score was calculated retrospectively, and a logistic regression model was used to assess the diagnostic accuracy of the clinical parameters. Results: A total of 107 patients were analysed. Among them, 31(28.97%) had acute appendicitis and 34 (31.77%) had acute mesenteric adenitis as the final diagnosis. The positive predictive value of clinical diagnosis was 0.91 for acute appendicitis and 0.73 for acute mesenteric adenitis, for Paediatric Appendicitis Score was 0.77 and for the predictive model to diagnose acute mesenteric adenitis was 0.89. Ultrasound had a positive predictive value of 0.97 to diagnose acute appendicitis and 0.94 to diagnose acute mesenteric adenitis. Conclusion: Although several clinical parameters show promise in differentiating AA from AMA, relying solely on clinical differentiation is not accurate enough to prevent diagnostic errors. It is still recommended to utilise abdominal ultrasound for the assessment of abdominal pain in children.